Effect of cooking on aroma profiles of Chinese foxtail millet (Setaria italica) and correlation with sensory quality. (15th August 2019) - Bi, Shuang; Wang, Aojidong; Wang, Yanping; Xu, Xinxing; Luo, Dongsheng; Shen, Qun; Wu, Jihong
Highlights: The effects of cooking methods on volatile compounds in millet were investigated. The aroma-active components of millet after cooking were identified. The aroma attributes and sensory attributes of millet after cooking were described. The role of volatile constituents in imparting aroma of millet was elucidated. Abstract: The effects of roasting, boiling, and freeze-drying after boiling on volatile aroma compounds in three varieties of Chinese foxtail millet ( Setaria italica ), namely, Jingu 21, Fenghonggu and Dongfangliang were determined. During boiling significant ( p < 0.05) increases in the contents of several unsaturated aldehydes, alcohols, and benzene derivatives were observed, unlike roasting that mainly increased in the contents of pyrazines. Freeze-drying after boiling decreased complexity of flavors, with a reduction in the contents of volatile compounds. Descriptive sensory analysis showed that the maximum intensity of 'popcorn-like' and 'smoky' odors was observed for roasted samples, whereas boiled and pre-boiled-freeze-dried samples were characterized by 'boiled rice' and 'boiled potatoes' odors, respectively. A correlation of odor-active profile data with descriptive sensory analysis clearly established the role of pyrazines such as 2-ethyl-3, 5-dimethylpyrazine in contributing to the 'popcorn-like', 'boiled beans', and 'smoky' odors, whereas dienals such as ( E, E )-2, 4-decadienal were responsible for the 'boiled rice' aroma.